2009
DOI: 10.1002/cjce.20238
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption kinetics of cadmium ions onto powdered corn cobs

Abstract: Environmental pollution caused by the presence of toxic materials such as cadmium is becoming global problem and concern. This paper presents a report on kinetics of Cd 2+ removal from aqueous solutions through adsorption using powdered corn cobs (PCC). Corn cobs were collected from a selected location, washed to remove sand, air dried, ground and sieved into different particle sizes. The selected properties of PCC were determined using acid digestion method. Adsorption capacities through kinetics of Cd 2+ rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 64 publications
1
3
0
Order By: Relevance
“…6 shows that the highest efficiency of Cd removal by (nMgO and Bentonite) nano-composite was at temperature of 307 K and pH 9. These findings are coincided with Ismail et al ( 2009) [42] who found an increase of Cd adsorption by powdered corn cobs with increasing temperature from 25 to 55 o C. The enhanced adsorption at higher temperature is attributed to the increase of surface reaction and kinetic energy of sorbate [43].…”
Section: Effect Of Temperature On CD Sorption By Nano-compositesupporting
confidence: 89%
“…6 shows that the highest efficiency of Cd removal by (nMgO and Bentonite) nano-composite was at temperature of 307 K and pH 9. These findings are coincided with Ismail et al ( 2009) [42] who found an increase of Cd adsorption by powdered corn cobs with increasing temperature from 25 to 55 o C. The enhanced adsorption at higher temperature is attributed to the increase of surface reaction and kinetic energy of sorbate [43].…”
Section: Effect Of Temperature On CD Sorption By Nano-compositesupporting
confidence: 89%
“…The figures show that the char retained the form and structure of the fresh cobs as received. Unlike in related research studies [18] the cobs were not shredded. They were carbonised and activated as received because the authors envisaged that the fibrous structure of the cobs retained after the activation will allow infiltration of liquids to ensure adsorption at the active sites of the products.…”
Section: Activated Carbons Obtained From the Corn Cobsmentioning
confidence: 97%
“…It seems not to influence the biosorption parameters in the range of 20-35 0 C (Aksu et al, 1992), but it mostly depends upon the features of the heavy metal. Ismail et al (2009) investigated the batch experiment temperature impacts of powdered maize cobs for cadmium ion removal. The greater adsorption capacity for cadmium ions was observed 18.15 mg/g at 250 °C and 25.51 mg/g at 550 °C.…”
Section: Factor Affecting Biosorptionmentioning
confidence: 99%